Molecular‐level Designed Polymer Electrolyte for High‐Voltage Lithium–Metal Solid‐State Batteries - Wang, Chao; Liu, Hong; Liang, Yuhao; Li, Dabing; Zhao, Xiaoxue; Chen, Jiaxin; Huang, Weiwei; Gao, Lei; Fan, Li‐Zhen (Advanced functional materials, 2023)
In solid polymer electrolytes (SPEs) based Li–metal batteries, the inhomogeneous migration of dual‐ion in the cell results in large concentration polarization and reduces interfacial stability during cycling. A special molecular‐level designed polymer electrolyte (MDPE) is proposed by embedding a special functional group (4‐vinylbenzotrifluoride) in the polycarbonate base. In MDPE, the polymer matrix obtained by copolymerization of vinylidene carbonate and 4‐vinylbenzotrifluoride is coupled with the anion of lithium‐salt by hydrogen bonding and the “σ‐hole” effect of the CF bond. This intermolecular interaction limits the migration of the anion and increases the ionic transfer number of MDPE (tLi+ = 0.76). The mechanisms of the enhanced tLi+ of MDPE are profoundly understood by conducting first‐principles density functional theory calculation. Furthermore, MDPE has an electrochemical stability window (4.9 V) and excellent electrochemical stability with Li–metal due to the CO group and trifluoromethylbenzene (ph‐CF3) of the polymer matrix. Benefited from these merits, LiNi0.8Co0.1Mn0.1O2‐based solid‐state cells with the MDPE as both the electrolyte host and electrode binder exhibit good rate and cycling performance. This study demonstrates that polymer electrolytes designed at the molecular level can provide a broader platform for the high‐performance design needs of lithium batteries. Molecular‐level designed polymer electrolyte with high ionic transfer number and wide electrochemical window is developed by molecular level design and used as a binder for the cathode active material of lithium‐ion batteries. The all‐solid‐state lithium metal battery with high reversible capacity and low interfacial impedance is prepared by the coating process that improved the cycle capability and energy density of the full battery.